Effect of Training Based on Choice Theory on Health-Promoting Lifestyle Behaviors among Menopausal Women - Anahita Ensan; Rahele Babazadeh; Hamidreza Aghamohammadian; Monavar Afzal Aghaei (Mashhad University of Medical Sciences, 2018)
Background & aim: Menopause is considered as a stage of life that is often encountered by all women with symptoms as hot flashes, sweating, palpitations, sleep disorders, and urinary tract problems. The improvement of health-promoting lifestyle behaviors is one of the effective measures to moderate these symptoms by facilitating the women to enhance their lifestyle behaviors through making proper choices. The aim of this study was to measure the effect of training based on choice theory on health-promoting lifestyle behaviors in menopausal women. Methods: This two-group pretest-posttest design was conducted on 40 menopausal women within the age range of 45-55 years, referring to healthcare centers in Mashhad, Iran, in 2016. The subjects were randomly assigned into intervention and control groups using simple random sampling method. The data collection instruments included a demographic questionnaire, a menopause knowledge/attitude questionnaire, as well as Health-Promoting Lifestyle Profile II (HPLPII), which consisted of six dimensions of nutrition, physical activity, responsibility for health, stress management, interpersonal relationships, and spiritual growth. The intervention group received training in seven 90-minute sessions based on choice theory. The data were analyzed in SPSS software using descriptive statistics, Mann-Whitney U test, independent t-test, paired sample t-test, and Friedman test. Results: According to the results, after the intervention, the mean scores of total health-promoting lifestyle behaviors (P